How the Leopard Hides Its Spots: ASIP Mutations and Melanism in Wild Cats - Schneider, Alexsandra; David, Victor A.; Johnson, Warren E.; O'Brien, Stephen J.; Barsh, Gregory S.; Menotti-Raymond, Marilyn; Eizirik, Eduardo (PLOS ONE, 2012)
The occurrence of melanism (darkening of the background coloration) is documented in 13 felid species, in some cases reaching high frequencies at the population level. Recent analyses have indicated that it arose multiple times in the Felidae, with three different species exhibiting unique mutations associated with this trait. The causative mutations in the remaining species have so far not been identified, precluding a broader assessment of the evolutionary dynamics of melanism in the Felidae. Among these, the leopard (Panthera pardus) is a particularly important target for research, given the iconic status of the ‘black panther’ and the extremely high frequency of melanism observed in some Asian populations. Another felid species from the same region, the Asian golden cat (Pardofelis temminckii), also exhibits frequent records of melanism in some areas. We have sequenced the coding region of the Agouti Signaling Protein (ASIP) gene in multiple leopard and Asian golden cat individuals, and identified distinct mutations strongly associated with melanism in each of them. The single nucleotide polymorphism (SNP) detected among the P. pardus individuals was caused by a nonsense mutation predicted to completely ablate ASIP function. A different SNP was identified in P. temminckii, causing a predicted amino acid change that should also induce loss of function. Our results reveal two additional cases of species-specific mutations implicated in melanism in the Felidae, and indicate that ASIP mutations may play an important role in naturally-occurring coloration polymorphism.